Effect of Cu-Zn coated steel fibers on high temperature resistance of reactive powder concrete. (March 2019) - Scheinherrová, Lenka; Vejmelková, Eva; Keppert, Martin; Bezdička, Petr; Doleželová, Magdaléna; Krejsová, Jitka; Grzeszczyk, Stefania; Matuszek-Chmurowska, Aneta; Černý, Robert
Abstract: Even though many studies have reported about the impacts of shape, length and distribution of steel fiber reinforcement on global concrete properties, there is a lack of information about the influence of coating type of steel fibers on high temperature resistance of concrete. This paper describes the effect of Cu-Zn coated steel fibers on selected properties of reactive powder concrete (RPC) after exposure to elevated temperatures. The initial corrosion of zinc in Cu-Zn surface layer is found to be already activated by the alkaline environment of the fresh concrete. The RPC samples reinforced with Cu-Zn coated steel fibers are heated to 600 °C and 1000 °C, and the influence of thermal load on microstructure, basic physical, mechanical, thermal and durability properties is analyzed. Based on the obtained results, it can be concluded that the maximal temperature to maintain effectiveness of the RPC reinforced with Cu-Zn steel fibers is 600 °C.